Age-adjusted Charlson Comorbidity Index predicts prognosis of laryngopharyngeal cancer treated with radiation therapy. (2nd December 2017) - Takemura, Kazuya; Takenaka, Yukinori; Ashida, Naoki; Shimizu, Kotaro; Oya, Ryohei; Kitamura, Takahiro; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract: Objectives: To examine the ability of comorbidity indices to predict the prognosis of laryngopharyngeal cancer and their association with treatment modalities. Methods: This retrospective study included 198 patients with laryngeal, hypopharyngeal, and oropharyngeal cancers. The effect of comorbidity indices on overall survival between surgery and (chemo)-radiation therapy ((C)RT) groups was analyzed. The cumulative incidence rates for cancer mortality and other mortalities according to the age-adjusted Charlson Comorbidity Index (ACCI) and Charlson Comorbidity Index (CCI) were compared. Results: Univariate survival analyses showed a significant association between the ACCI and overall survival in the (C)RT group, but not in the surgery group. The association between the CCI and overall survival was not significant in either group. In multivariate analyses, a high ACCI score was an independent prognostic factor in the (C)RT group (HR 2.89, 95% confidence interval (CI) 1.28–6.49), but not in the surgery group (HR 1.39, 95%CI 0.27–5.43). The higher ACCI group had increased mortality from other causes compared with the lower ACCI group (5-year cumulative incidence, 8.5% and 17.8%, respectively, p = .003). Conclusion: The ACCI was a better prognostic factor than the CCI. Surgery may be more beneficial than radiation for patients with a high ACCI.